2017
DOI: 10.1007/s12035-017-0589-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton-Associated Risk Modifiers Involved in Early and Rapid Progression of Sporadic Creutzfeldt-Jakob Disease

Abstract: A high priority in the prion field is to identify pre-symptomatic events and associated profile of molecular changes. In this study, we demonstrate the pre-symptomatic dysregulation of cytoskeleton assembly and its associated cofilin-1 pathway in strain and brain region-specific manners in MM1 and VV2 subtype-specific Creutzfeldt-Jakob disease at clinical and pre-clinical stage. At physiological level, PrP interaction with cofilin-1 and phosphorylated form of cofilin (p-cofilin(Ser3)) was investigated in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
1
13
0
1
Order By: Relevance
“…Recently, it was demonstrated that cofilin can associate with the cellular form of prion protein (PrP C ) in sporadic Creutzfeldt-Jakob disease subtypes and higher levels of SSH1 could be detected in disease samples. This study creditably underscores the cofilin-SSH1 interaction as a contributor of neurodegeneration [ 94 ]. Further, PTEN is a lipid and protein phosphatase that inhibits PI3/AKT signaling and inhibiting PTEN has neuroprotective effects in an AD mouse model, amyloid-β toxicity, a PD model, and lab models of spinal muscular atrophy [ 95 ].…”
Section: Dusps In Protein Aggregation Diseasessupporting
confidence: 68%
“…Recently, it was demonstrated that cofilin can associate with the cellular form of prion protein (PrP C ) in sporadic Creutzfeldt-Jakob disease subtypes and higher levels of SSH1 could be detected in disease samples. This study creditably underscores the cofilin-SSH1 interaction as a contributor of neurodegeneration [ 94 ]. Further, PTEN is a lipid and protein phosphatase that inhibits PI3/AKT signaling and inhibiting PTEN has neuroprotective effects in an AD mouse model, amyloid-β toxicity, a PD model, and lab models of spinal muscular atrophy [ 95 ].…”
Section: Dusps In Protein Aggregation Diseasessupporting
confidence: 68%
“…[ [259][260][261][262][263][264] Familial Abnormal F-actin dynamics in interphase cells affect endocytic recycling. [267,268] Lissencephaly-1/OMIM#607432 Lissencephaly-1 (LIS1)(P43034)/PAFAH1B1…”
Section: Cytoskeletal Abnormalities In Neurological Diseasesmentioning
confidence: 99%
“…It is interesting to note that alterations in neuronal cytoskeleton physiology can also be used to monitor disease progression since they can even be detected in pre-clinical stages of specific neurodegenerative diseases. This is the case with the MM1 and VV2 subtypes of sporadic Creutzfeldt-Jakob disease (CJD), where cytoskeleton assembly dysregulation mediated by alterations in cofilin-1 and its upstream regulators LIMK1, SSH1, Rock2, and APP has been described in both mice and humans [268]. Importantly, the finding of mechanistic relationships between cofilin-1 phosphorylation, its interaction with the prion protein PrP C , and alterations in activated microglia, as well as the accumulation of a dense form of F-actin, were found in frontal cortex and cerebellum samples from individuals at the pre-clinical stage, highlighting the potential for early diagnosis held by the analysis of cytoskeleton alterations in neurodegeneration.…”
Section: Neuronal Cytoskeleton Abnormalities Generate Neurodegenerationmentioning
confidence: 99%
“…Patient cohort processing, neuropathological examination and brain tissue collection for this study were all conducted as previously described [90,91]. The post-mortem interval was between 3 and 18 h. Both spAD and rpAD samples had AD pathologies with Braak stage ≥ V. The samples for AD subtypes were included without co-pathologies.…”
Section: Patient Cohorts and Rpad/spad/scjd Subtype Characterizationmentioning
confidence: 99%